2016
DOI: 10.1038/ncomms11226
|View full text |Cite
|
Sign up to set email alerts
|

Ndfip-mediated degradation of Jak1 tunes cytokine signalling to limit expansion of CD4+ effector T cells

Abstract: Nedd4 family E3 ubiquitin ligases have been shown to restrict T-cell function and impact T-cell differentiation. We show here that Ndfip1 and Ndfip2, activators of Nedd4 family ligases, together limit accumulation and function of effector CD4+ T cells. Using a three-part proteomics approach in primary T cells, we identify stabilization of Jak1 in Ndfip1/2-deficient T cells stimulated through the TCR. Jak1 degradation is aborted in activated T cells that lack Ndfips. In wild-type cells, Jak1 degradation lessens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 60 publications
2
38
0
Order By: Relevance
“…Ndfip1-deficient CD4+ T cells secrete excess IL-4242829 and this can impact the differentiation of alternate cell fates or affect the activation state of T cells. For Th17 cells, IL-4 has been shown to both promote or inhibit their differentiation27313335.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ndfip1-deficient CD4+ T cells secrete excess IL-4242829 and this can impact the differentiation of alternate cell fates or affect the activation state of T cells. For Th17 cells, IL-4 has been shown to both promote or inhibit their differentiation27313335.…”
Section: Resultsmentioning
confidence: 99%
“…This study focused predominantly on Ndfip1, an activator of Itch catalytic activity24284849. It has been shown that the loss of Ndfip1 globally, or following conditional deletion in T cells, causes spontaneous autoinflammatory disease that is associated with high numbers of activated CD4 T cells, increased numbers of Th1, Th2, and Th17 cells, and premature death24262729.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NDFIP1 binds to and activates HECT-type E3 ubiquitin ligases (Mund and Pelham, 2009; Riling et al, 2015), thereby triggering ubiquitin-medi- ated degradation of key T cell differentiation regulators, including JUNB, RORγt, and JAK1 (Layman et al, 2017b; O’Leary et al, 2016; Oliver et al, 2006). In T cells, NDFIP1 primarily recruits and activates the HECT-type E3 ligase ITCH (Oliver et al, 2006).…”
Section: Introductionmentioning
confidence: 99%